A view from the top: State perspectives on legitimacy and the mine development process. Issue 94 (April 2019) - Poelzer, Gregory
Highlights: Throughput legitimacy points to qualities in the policy process that are underdeveloped in input legitimacy. Institutional context plays a large role in the perception state officials on legitimacy. Moving policy issues away from the political area to professional bureaucrats may decrease legitimacy. Abstract: Legitimacy is typically given to an authority by a subject. In most cases, the state. However, different governance structures alter the role of the state and the support of some policy decisions rests on the actions of others. In mine development, government sits in an interesting position. As the permitting authority, government holds the responsibility for determining the paths companies must travel to open and operate a mine. At the same time, mining companies engage in extra-legislative activities to build public support and move the process forward. Therefore, the state may no long control the legitimacy of the mine development process. Conducting interviews with state officials in two jurisdictions, Saskatchewan, Canada and Norrbotten, Sweden, this study investigates whether legitimacy issues exist from the perspective of the authority. Focusing on participation, influence, transparency, accountability, and responsiveness, the study determines first if shared conceptions of these factors exists amongst officials and then whether they viewed the process operating in a manner that matches these shared conceptions. The most significant differences in views occurred in Norrbotten where the results on throughput legitimacy pointed to legitimacy issues from the perspective of the state, particularly with other government agencies.